The role of protein globule in firefly luciferase catalysis - Ugarova, Natalia N.; Lomakina, Galina Yu (Photochemistry and photobiology, 2024)
The important role of the dynamic structure of firefly luciferase in enzyme functioning is a subject of this literature review. Due to the domain alternation, the optimal configuration of the active site is created for each stage of the luciferin oxidation. The diversity of bioluminescence spectra is explained by the combined emission of several coexisting forms of electronically excited oxyluciferin. The superposition of two or three emitter forms recorded in the bioluminescence spectra indicates that different luciferase conformers coexist in the reaction medium in dynamic equilibrium. The relationship between the thermal stability of the protein globule and the bioluminescence spectra is also discussed